Research on condensation phenomenon during energy-saving shutdown of base station - Jixiang FU; Ruiyan ZHANG; Min ZHANG; Lin TAO; Wei DENG (Dianxin kexue)
5G base station has a significant increase in its full-load power consumption compared to 4G base stations due to multiple transceiver channels, wide bandwidth, high traffic and high transmission power.In the early stage of 5G development, since there may be scenarios without users for a long time in the current network base stations, intermittent shutdown of the base stations can play a role in energy saving.However, the intermittent shutdown of the base station saves energy and condensation occurs inside the equipment , which will cause corrosion and burn down of devices and PCB, resulting in the failure of base station equipment.The basic principle of condensation was introduced, the condensation experiment was designed and the comparative verification was carried onto the base station equipment, the causes of condensation on the base station equipment were analyzed, and finally the suggestion for the use scheme of the base station equipment to avoid condensation was given.